What Does Debt Relief Do for Development? Evidence from India’s Bailout Program for Highly-Indebted Rural Households - Kanz, Martin (2013)
This paper studies the impact of a large debt relief program, intended to attenuate investment constraints among highly-indebted households in rural India. It isolates the causal effect of bankruptcy-like debt relief settlements using a natural experiment arising from India's Debt Relief Program for Small and Marginal Farmers -- one of the largest debt relief initiatives in history. The analysis shows that debt relief has a persistent effect on the level of household debt, but does not increase investment and productivity as predicted by theories of debt overhang. Instead, the anticipation of future credit constraints leads to a greater reliance on informal financing, lower investment and a decline in productivity among bailout recipients. The results suggest that one-time settlements may be insufficient to incentivize new investment, but can have significant real effects through their impact on borrower expectations.